Pre-shot combinations and game-related statistics discriminating between winners and losers depending on the game location during the NBA COVID-19 season - Bustamante-Sánchez, Alvaro; Gomez-Ruano, Miguel-Angel; Clemente-Suárez, Vicente Javier; Jiménez-Sáiz, Sergio L. (Frontiers in Physiology, 2022)
Basketball in performance depends on numerous factors, where a stable trend was identified by winning teams with better performances in shooting effectiveness and rebounding. However, there is a need for a better understanding of pre-shot combinations that lead to these performance trends. This study aimed to analyse NBA teams’ game-related statistics, pre-shooting combinations, and pick-and-roll differences between winning and losing teams (considering the context: playing at home, away, or in a neutral court) during the COVID-19 season. A retrospective cross-sectional study of the 2019-2020 NBA season (906 games) was carried out. Game-related statistics were gathered from the private company InStat (https://basketball.instatscout.com/). The discriminant analysis and binary logistic regression models were run in order to discriminate the most important features for winning teams depending on the game location. The results showed that defensive rebounds and three-point shooting percentage remain the most important variables that best discriminated winners and losers independently of the game location context. The main results showed that winning teams had a better shooting percentage based on 3-pointers, catch-and-shot actions, cuts, pick-and-roll efficacy, and uncontested shots based on a better collective behaviour after a successful space creation dynamic through a tactical functional unit. At the same time, teams would need players with the ability to clear those possessions in which the opponents force to an isolation or a contested shot. From a practical application perspective, coaches should focus on composing a team with good shooters, skilled players in isolations and a good game-time pick-and-roll strategy.